ChemInform Abstract: Enantioconvergent Synthesis of Functionalized γ‐Butyrolactones via (3 + 2)‐Annulation. Issue 27 (18th June 2015) - Goodman, C. Guy; Walker, Morgan M.; Johnson, Jeffrey S.
Abstract A chiral N‐heterocyclic carbene‐catalyzed a3 → d3‐umpolung addition of α, β‐enals to racemic α‐keto esters gives access to γ‐butyrolactones with high regio‐, diastereo‐, and enantiocontrol.